study on Trust Management System for Ubiquitous and Pervasive IoT Application - et. al., Anup Patnaika , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
IoT (Internet of things) is one of prominent technologies for provisioning of services through smart, intelligent and heterogeneous devices connected to each other via internet. With environmental influences, the widely used IoT applications are much prone to security and privacy related problems. In order to address these issues, many solutions were proposed in the recent past but most of these models have not fulfilled yet all the promises of IoT requirements. Furthermore, considering the characteristics of IoT involving heterogeneity, dynamic, mobility of nodes, energy constraint, less computing power devices, then it’s challenging to propose dynamic trust management system (TMS). This paper contributes the comparison study of existing trust management approaches applied to various IoT based applications.Further, it highlights open issues, research challenges and provides the future direction to address the current research challenges through research model, holistic trust management.